Individual and Organizational Contributions to Educator Stress: The Roles of Organizational Health and Self‐Invalidation - Ruork, Allison K.; Rizvi, Shireen L.; Mui, Anna; Nadeem, Erum; Shernoff, Elisa S. (Psychology in the schools, 2025)
ABSTRACT Chronic stress among educators is associated with burnout, absenteeism, and turnover. Identification of the contributors to educator stress is critical to guide prevention and intervention efforts. However, despite stress being conceptualized as a complex and dynamic process, the literature has generally focused on cross‐sectional studies with inadequate attention to the interaction between individual and organizational factors. The biosocial model of emotion dysregulation posits that invalidating environments and systems (e.g., school organizational health) interact with individual vulnerabilities and behavior (e.g., self‐invalidation), contributing to problematic emotion experiences and use of unhelpful coping strategies. Educators (N = 39) from schools within one high poverty district participated in an 8‐week Dialectical Behavior Therapy (DBT) skills‐based intervention and contributed data at pre and post. Linear regressions and t‐tests evaluated whether there was preliminary support for the biosocial model with regard to the development of educator stress. This includes examining whether educators tended to self‐invalidate, if organizational health was associated with educator stress, and if there were changes in self‐invalidation over time. Results suggest organizational health was associated with educator stress at baseline (p < 0.001), but self‐invalidation was not (p = 0.07). However, self‐invalidation did significantly improve over the course of the intervention (Cohen's d = 2.27), while perceived organizational health declined (Cohen's d = 0.62). Results provide additional support for the role organizational health plays in the development of stress and burnout among educators, as well as preliminary support for improvements in self‐invalidation among educators participating in a DBT skills‐based intervention. Summary Improvements in self‐invalidation over time suggests that directly addressing how educators perceive and respond to their own emotions and experiences (a core Dialectical Behavior Therapy [DBT] concept) can be an important part of reducing stress. Schools could consider incorporating DBT‐informed self‐validation practices into professional development or wellness programs to help educators manage stress more effectively. Given organizational health declined over time, interventions focusing on personal coping skills may be necessary but insufficient to sustain a healthy work environment without integrated approaches that support personal well‐being and the broader school climate.